2018
DOI: 10.1016/j.dci.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

TRAF3 enhances STING-mediated antiviral signaling during the innate immune activation of black carp

Abstract: Tumor necrosis factor receptor-associated factor 3 (TRAF3) is a main regulator of antiviral and anti-inflammatory pathways in mammals, which is considered to induce type I interferon (IFN) activation and negatively regulate the activation of the canonical and non-canonical NF-κB pathways. To elucidate its function in teleost fish, TRAF3 homologue of black carp (Mylopharyngodon piceus) has been cloned and characterized in this study. The open reading frame (ORF) of black carp TRAF3 (bcTRAF3) consists of 1722 nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated the crucial role of TRAF3 , a multifunctional immune molecule, in antiviral innate immunity [ 26 , 27 ]. Acting as the adaptor protein that links MAVS to mitochondria, TRAF3 facilitates K63-linked ubiquitination, thereby activating IFN-I [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the crucial role of TRAF3 , a multifunctional immune molecule, in antiviral innate immunity [ 26 , 27 ]. Acting as the adaptor protein that links MAVS to mitochondria, TRAF3 facilitates K63-linked ubiquitination, thereby activating IFN-I [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Pf _TRAF4a might play positive regulatory roles in NF-κB signaling like other species [55,73]. The number of RING finger, zinc finger, TRAF-BIRC_3, coiled-coil and MATH domains of grouper, black carp, Nile tilapia, human and yellow catfish TRAF2 proteins is 1-2-0-1-1, 1-0-1-0-1, 1-1-1-0-1, 1-1-1-0-1 and 1-2-1-0-1, respectively [66,[74][75][76]. Among them, the grouper [66] and the black carp [74] TRAF2 are localized in the cytoplasm, and the human [76] and Nile tilapia [75] TRAF2 are localized in the nucleus and cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of TRAF3 in teleost compared with its mammalian counterpart is still largely unknown. In recent years, the TRAF3 homologues have been cloned and characterized in several species for instance, common carp ( Cyprinus carpio ) (Feng et al, 2011) and humphead snapper ( Lutjanus sanguineus ) (Cai et al, 2015), black carp (Wang et al, 2018), Nile tilapia ( Oreochromis niloticus ) (Han et al, 2020). In previous studies, it has been reported that some of the key components of RLR signalling such as MAVS, TRAF3, TRIF and IRF3 are found to be associated with TANK, where TANK is recruited into regulating phosphorylation of IRF3 and IFN induction (Gatot et al, 2007; Guo & Cheng, 2007).…”
Section: Introductionmentioning
confidence: 99%